Tantangan desentralisasi asimetris di Aceh perspektif Sadd Az-Zari’ah - 'Ainun Najah, Faza (LP3M Universitas Islam Zainul Hasan Genggong, 2024)
Asymmetric decentralization in Aceh is an effort to grant or transfer special authority which is considered as an alternative way with the aim of solving problems between central and regional relations in accordance with the 1945 Constitution of the Republic of Indonesia, precisely in Article 18 which regulates decentralization in Indonesia. This research focuses on the concept of sadd az-zari'ah towards asymmetrical decentralization in Aceh, the research method used in this research is literature. Data collection techniques from various leterature such as books, and journals and others that have a relationship with this research. The results of the study concluded that the challenge of asymmetrical decentralization in Aceh was initially considered valid in sharia, but sometimes it can produce losses. However, the harm is more modest compared to the good and it can be interpreted that the harm is to prevent greater harm. The concept of asymmetrical decentralization in Aceh is considered to be more protective of the harm that will be caused seeing the history of the relationship between Aceh and the Indonesian government in accordance with the rules if two mafsadat collide, choose the lighter mafsadat.